Impact of patient counseling on medication adherence and drug resistance patterns in tuberculosis patients - Sanatkumar Bharamu Nyamagoud; Princy Domnic Dsouza; Sai Phalguna Prakash Chitralu; Kadambari Solankure; Agadi Hiremath Viswanatha Swamy (Monaldi Archives for Chest Disease)
Tuberculosis (TB) remains a primary global health concern, with non-adherence to anti-TB therapy contributing to prolonged infectiousness, treatment failure, and unfavorable outcomes. Despite established treatment protocols, adherence remains suboptimal due to patient-related, healthcare system, and socioeconomic barriers. This study aimed to identify key factors contributing to non-adherence and to evaluate the impact of structured patient counselling on treatment adherence. A cross-sectional observational study was conducted at Vivekananda General Hospital, Hubballi, India, involving 80 hospitalized TB patients. Data collection included demographic details and medication adherence scores, measured before and one month after counseling using the Medication Adherence Report Scale. Statistical analysis was performed using SPSS version 27.0, with Pearson’s correlation applied to assess changes in adherence. The mean adherence scores significantly increased from 4.24±1.452 to 7.05±1.525 following counseling (p=0.006). The most commonly reported barriers to adherence included forgetfulness (62.5%), limited access to healthcare (50%), and poor communication with healthcare providers (47.75%). These findings highlight the effectiveness of structured counseling in improving adherence among TB patients. Addressing both individual and systemic barriers through targeted counseling interventions should be considered an integral component of TB care strategies.